3m+4=4m+4

Simple and best practice solution for 3m+4=4m+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+4=4m+4 equation:


m in (-oo:+oo)

3*m+4 = 4*m+4 // - 4*m+4

3*m-(4*m)-4+4 = 0

3*m-4*m-4+4 = 0

-1*m = 0 // : -1

m = 0

m = 0

See similar equations:

| 7a+9=5a-11 | | 4-7b=2b-95 | | -m+6=-34+4m | | 2+6k=k+22 | | -2-5x=-x-18 | | n+10=6n-25 | | 4k+2=6k+18 | | 4b+8=-64-5b | | -8+3t=-5t-64 | | 4d-9=-4d+71 | | 7k+7=11+3k | | 6k+3=23-4k | | 4a+5=-39-7a | | -7d-2=4d+75 | | 8-5w=5w-32 | | -2d+2=-7d-13 | | 1+6d=d+1 | | 3a+3=-2a-12 | | 4t+7=5+5t | | 6k-6=3k+3 | | 4a+10=7a-2 | | 5-4k=5k+50 | | -4t+2=112+6t | | -2+t=2t-1 | | 5x+2=2x+26 | | -8+2m=-2m+12 | | x+4=6x+4 | | 7+6k=-7k+7 | | 2m+2=-7m+56 | | 3a+3=-5a-37 | | 10-4t=-3t+1 | | 2b-1=-b+29 |

Equations solver categories